Validation of Susceptibility Loci for Vitiligo Identified by GWAS in the Chinese Han Population - Cheng, Lu (Front Genet, 2020)
Forty-nine susceptible loci have been reported to be significantly associated with vitiligo by genome-wide association studies (GWASs) in European-derived whites. To date, some of these reported susceptibility loci have not yet been validated in the Chinese Han population. The purpose of this study was to examine whether the 16 reported susceptible loci in European-derived whites were associated with vitiligo in the Chinese Han population. Imputation was performed using our previous GWAS dataset by IMPUTE v2.2.2. The 16 imputed top single-nucleotide polymorphisms (SNPs) with suggestive signals, together with the reported SNPs, were genotyped in a total of 2581 patients and 2579 controls by the Sequenom MassARRAY system. PLINK 2.0 software was used to perform association analysis. The dbSNP database, HaploReg, and eQTL data were adopted to annotate the biological function of the SNPs. Finally, four SNPs from three loci were significantly associated with vitiligo, including rs3747517 (P = 1.29 × 10(–3), OR = 0.87) in 2q24.2, rs4807000 (P = 7.78 × 10(–24), OR = 0.66) and rs6510827 (P = 3.65 × 10(–5), OR = 1.19) in 19p13.3, and rs4822024 (P = 6.37 × 10(–10), OR = 0.67) in 22q13.2. According to the dbSNP database, rs3747517 is a missense variant of IFIH1, rs4807000 and rs6510827 are located in TICAM1, and rs4822024 is located 6 kb upstream of TEF. Further bioinformatics analysis by HaploReg and eQTL found that rs4807000, rs6510827, and rs4822024 are involved in regulating gene expression. Our study revealed the strong association of 2q24.2 (rs3747517), 19p13.3 (rs4807000, rs6510827), and 22q13.2 (rs4822024) with the risk of vitiligo in the Chinese Han population, which implicates common factors for vitiligo across different ethnicities, and helps expand the understanding of the genetic basis of this disease.